2007
DOI: 10.1088/1009-9271/7/2/01
|View full text |Cite
|
Sign up to set email alerts
|

The Long-term Survival Chances of Young Massive Star Clusters

Abstract: We review the long-term survival chances of young massive star clusters (YMCs), hallmarks of intense starburst episodes often associated with violent galaxy interactions. We address the key question as to whether at least some of these YMCs can be considered protoglobular clusters (GCs), in which case these would be expected to evolve into counterparts of the ubiquitous old GCs believed to be among the oldest galactic building blocks. In the absence of significant external perturbations, the key factor determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 155 publications
(352 reference statements)
3
74
0
Order By: Relevance
“…de Grijs et al 2003;Elmegreen et al 2005). These clusters could be the progenitors of the old globular clusters observed in most galaxies today (de Grijs & Parmentier 2007), thus providing further evidence for the link between the starburst phenomenon and the formation of galaxies. Moreover, star-forming regions with properties consistent with the more massive HII regions detected locally are observed up to z ∼ 5 (Swinbank et al 2009), and local dwarf galaxies have been identified as scaled down analogs of clumpy starforming galaxies at high redshift (Elmegreen et al 2009).…”
Section: Introductionmentioning
confidence: 67%
“…de Grijs et al 2003;Elmegreen et al 2005). These clusters could be the progenitors of the old globular clusters observed in most galaxies today (de Grijs & Parmentier 2007), thus providing further evidence for the link between the starburst phenomenon and the formation of galaxies. Moreover, star-forming regions with properties consistent with the more massive HII regions detected locally are observed up to z ∼ 5 (Swinbank et al 2009), and local dwarf galaxies have been identified as scaled down analogs of clumpy starforming galaxies at high redshift (Elmegreen et al 2009).…”
Section: Introductionmentioning
confidence: 67%
“…Those clusters that survive the infant mortality phase will be subject to the processes driving longer-term star cluster dissolution (see for reviews de Grijs & Parmentier 2007;de Grijs 2010). The longer-term dynamical evolution of star clusters is determined by a combination of internal and external timescales.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, an age effect could be responsible: field stars are older on average because field stars are the relics of dissolved star clusters whose lifetimes of order 10 Myr are longer than O-star lifetimes. Therefore, massive O stars may disappear before cluster dissolution and never contribute to the field population [11].…”
Section: Stellar Populationmentioning
confidence: 99%